Exploring Students Strategies in Learning English Vocabulary Through Reading Activities at SMPN 4 Koto Baru: Exploring Students Strategies in Learning English Vocabulary Through Reading Activities at SMPN 4 Koto Baru - nora lisma mayang sari; Zumrotun Luthfia; Dodi Widia Nanda (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Vocabulary mastery is essential for developing English language proficiency because it supports reading comprehension and other language skills. However, junior high school students frequently encounter difficulties in understanding unfamiliar vocabulary during reading activities. This study aimed to explore the vocabulary learning strategies employed by eighth-grade students while reading English texts at SMPN 4 Koto Baru. A descriptive qualitative design was adopted involving eleven eighth-grade students and one English teacher selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews and analyzed using Creswell’s qualitative data analysis procedures, including data organization, reduction, presentation, and conclusion drawing. The trustworthiness of the findings was ensured through source and technique triangulation. The findings revealed three main vocabulary learning strategies: (1) asking teachers and classmates for explanations, (2) guessing word meanings from contextual clues, and (3) using dictionaries to verify unfamiliar vocabulary. Asking teachers and classmates emerged as the dominant strategy because students perceived it as the fastest, easiest, and most reliable way to understand unfamiliar words. These findings indicate that students primarily rely on social interaction while gradually developing independent vocabulary learning through contextual guessing and dictionary use. The study recommends that English teachers foster greater learner autonomy by encouraging contextual inference and effective dictionary use alongside collaborative classroom learning.